ON SEDIMENT DEPOSITION AND NATURE OF THE PLATE BOUNDARY AT THE JUNCTION BETWEEN THE SUBMARINE LOMONOSOV RIDGE, ARCTIC OCEAN AND THE CONTINENTAL MARGIN OF ARCTIC CANADA/NORTH GREENLAND - Kristoffersen Y.; Mikkelsen N. (My University, 2006)
The first seismic reflection data from the shallowest part of the submarine Lomonosov Ridge north of Arctic Canada and North Greenland comprise two parallel single channel lines (62 and 25 km long, offset 580 m) acquired from a 10 day camp on drifting sea ice. The top of southern Lomonosov Ridge is bevelled (550 m water depth) and only thin sediments (< 50 ms) cover acoustic basement. We suggest erosion of a former sediment drape over the ridge crest was either by a grounded marine ice sheet extending north from Ellesmere Island and/or deep draft icebergs. More than 1 km of sediments are present at the western entrance to the deep passage between southern Lomonosov Ridge and the Lincoln Sea continental margin. Here, the uppermost part (+ 0.3 s thick) of the section reflects increased sediment input during the Plio-Pleistocene. The underlying 0.7 s thick succession onlaps the slope of a subsiding Lomonosov Ridge. An unconformity at the base of the sedimentary section caps a series of NW-SE grabens and mark the end of tectonic extension and block faulting of an acoustic basement represented by older margin sediments possibly followed by minor block movements in a compressional regime. The unconformity may relate to termination of Late Cretaceous deformation between Lomonosov Ridge and Alpha Ridge or be equivalent to the Hauterivian break-up unconformity associated with the opening of the Amerasia Basin. A flexure in the stratigraphic succession above the unconformity is most likely related to differential compaction, although intraplate earthquakes do occur in the area. © 2005 Elsevier B.V. All rights reserved.
Keywords: ARCTIC OCEAN; LOMONOSOV RIDGE; SEDIMENT DRIFT; SEISMIC REFLECTION; SHEARED MARGIN; Pleistocene; Hauterivian; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Mesozoic::Cretaceous::Lower::Hauterivian; Мезозой::Меловая::Нижний::Готеривский